Role of diagnostic laparoscopy in chronic abdominal pain: Experience in a rural area - Vijay Kanake; Vighnesh Sundaravadanam; Shubhangi Mangam; Vijay Bhalavi (Chronic Diseases Journal, 2023)
BACKGROUND: Chronic abdominal pain is a frequent cause of surgical consultation. This study is conducted to evaluate usefulness of laparoscopy in diagnosis of chronic abdominal pain so as to reduce suffering and depression associated with condition. This study aims to define the role of diagnostic laparoscopy in chronic abdominal pain.